A study of gay phenomenal among higher institution students in Sungai Petani area / Mohd Shahridzwan Mohd Sabri and Mohd Faizal Ismail - Mohd Sabri, Mohd Shahridzwan; Ismail, Mohd Faizal (2012)
Gay group is now widespread in many higher education institutions in Malaysia. Due to this alarming scenario that will give big impact to our country future development, the researchers have found a strong base to study on the causes of why this phenomenal happen among our future leaders, especially among higher institutions students. The purpose of this study is getting the most factors that contribute to the gay phenomenal. This study cover male student from Institut Perguruan Kampus Sultan Abdul Halim (IPGKSAH), Institute of Medical Science and Technology (AIMST) and Universiti Technologi MARA (UiTM), Kedah.The sample sizes of this study were 150 which come 50 each from higher instituions. The sampling techniques which is snowball sampling were used in this study in order to select the respondent. The questionnaire is divided into four sections which are Section A for demographic questions. Section B for general questions, Section C for personality, genetic factor and developmental experiences. In this study, data was analysed using Statistical Package for Social Science (SPSS) Version 16.0. This research will provide the advantages to the student, whereby the student can be preventing from involved in gay activity. When the institution aware regarding student involvement in gay activities, they can take preventive action through implementing strict punishment, rules and regulation and etc to combat the problem from the early stage. In this research, data collected through questionnaire.